Antusias Masyarakat terhadap Mahasiswa KKN 43 UINSU melalui Pengabdian di Lingkungan Desa Kota Rantang, Hamparan Perak yang Menjadi Obyek Penelitian - Noveria Fradila Noveria Fradila; Tuti Anggraini; Ayu Sundari; Muhammad Syawal Karo; Nur Atika Shofia Herman; Riska Dwi Prasasti (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
This paper aims to instill the values ​​of responsibility, independence, leadership and a sense of empathy, especially to students. This research was conducted by the Student Community Service Group of 43 UINSU, in Dusun V, Rantang City Village, Hamparan Perak. The method used in this study is a qualitative research method, with a qualitative descriptive approach. The data sources used are primary data sources and secondary data sources. The findings of this study are utilizing the natural environment as a direct data source and prioritizing behavioral processes in natural situations. Through this KKN activity, it has become a new hope for the village community because it has created positive activities such as the pious children's festival which was held at the Rantang City Village Mosque. The community is also helped in carrying out daily activities, for example, during the day the Student Community Service Program Group 43 helps the community to teach MDA and its tahfiz.